Dynamic transmission power switch for fast data collection in duty-cycled sensor networks. (2017) - Fan, Zuzhi
Battery-powered sensor networks are often duty-cycled to conserve nodes energy and prolong network lifetime. In such intermittently-connected networks, the waiting time over multi-hop data forwarding dominates delivery latency, which is the main challenge and unacceptable for delay-sensitive applications. In this work, we address the optimisation problem for duty-cycled sensor network with transmission power control. In particular, we propose dynamic transmission power switch (DTPS), a cross-layer approach which jointly considers power control with multi-parent forwarding for the fast data collection. In DTPS, each node dynamically selects a sequence of transmission pairs to deliver data packets. Extensive simulation results show that our scheme can reduce both delivery delay and energy consumption for data collection applications.